Fenomena Kemiskinan: Studi Pada Masyarakat Pemulung Di Panampu Kec.Tallo Kota Makassar - Fahiratun Afiat Muizunzila; Sam’un Mukramin; Kaharuddin Kaharuddin; Maemunah Maemunah (Jurnal Relasi Publik, 2023)
Scavenger societies are social groups that depend on the activities of collecting, sorting, and recycling used goods. They do this work as the main source of income. This research aims to understand the characteristics and role of scavenger communities in waste and environmental management. The research methods used include surveys, interviews, and field observations. The collected data is analyzed qualitatively by identifying the main themes that arise from the research results. The results show that scavenger communities have an important role in reducing waste and recycling used goods. They collect various types of materials such as paper, plastic, metal, and electronics that can be resold or recycled. Their work contributes to reducing the negative impact on the environment and sustainable waste management. However, scavenger communities also face challenges and obstacles in carrying out their work. They often experience unsafe working conditions and health risks due to exposure to hazardous materials. In addition, they also face limited access to public services and social stigma that can affect their daily lives.